Challenges assessing radiation risk in image-guided treatments—implications on optimisation of radiological protection. (11th July 2018) - Almén, A; Lundh, C; Båth, M
Abstract: The present work explores challenges when assessing organ dose and effective dose concerning image-guided treatments. During these treatments considerable x-ray imaging is employed using technically advanced angiographic x-ray equipment. Thus, the radiation dose to organs and the related radiation risk are relatively difficult to assess. This has implications on the optimisation process, in which assessing radiation dose is one important part. In this study, endovascular aortic repair treatments were investigated. Organ dose and effective dose were assessed using Monte Carlo calculations together with a detailed specification of the exposure situation and patient size. The resulting normalised organ dose and effective dose with respect to kerma-area product for patient sizes and radiation qualities representative for the patient group were evaluated. The variability and uncertainty were investigated and their possible impact on optimisation of radiation protection was discussed. Exposure parameters, source to detector distances etc varied between treatments and also varied between image acquisitions during one treatment. Thus the derived normalised organ dose and effective dose exhibited a large range of values depending greatly on used exposure parameters and patient configuration. The derived normalised values for effective dose varied approximately between 0.05 and 0.30 mSv per Gy·cm 2 when taking patient sizes and exposure parameters into consideration, the values for organ doses exhibited even larger variation. The study shows a possible systematic error for derived organ doses and effective dose up to a factor of 7 if detailed exposure or patient characteristics are not known and/or not taken into consideration. The intra-treatment variability was also substantial and the normalised dose values varied up to a factor of 2 between image acquisitions during one treatment. The study shows that the use of conversion factors that are not adapted to the clinic can cause the radiation dose to be exaggerated or underestimated considerably. A conclusion from the present study is that the systematic error could be large and should be estimated together with random errors. A large uncertainty makes it difficult to detect true differences in radiation dose between methods and technology—a prerequisite for optimising radiation protection for image-guided treatments.